2008
DOI: 10.1055/s-2008-1040296
|View full text |Cite
|
Sign up to set email alerts
|

Differenzierte operative und konservative Therapie der Spondylitis und Spondylodiscitis

Abstract: In the time from 1980 to 1987 58 patients underwent a conservative or operative treatment of spondylitis and spondylodiscitis according to the individual clinical and radiological features. In early or moderately advanced stages of the disease conservative therapy was performed. Under bedrest and antibacterial or tuberculostatic drug therapy bony fusion of the affected vertebral bodies was achieved in 50% of the pyogenic cases. In tuberculous spondylitis fusion rate was 83%. Persistent septic changes, progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
3

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 0 publications
0
12
0
3
Order By: Relevance
“…It necessitates several weeks of patient immobilisation followed by several months of brace treatment before firm bony union with the graft can be achieved [3]. In contrast to conservative therapy, the fusion rate increased to 90-100% [3,32]. In cases with multi-segmental involvement and longer fusion spans, however, there are higher rates of complications such as pseudarthrosis and bone graft displacement with subsequent kyphotic deformation [3].…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…It necessitates several weeks of patient immobilisation followed by several months of brace treatment before firm bony union with the graft can be achieved [3]. In contrast to conservative therapy, the fusion rate increased to 90-100% [3,32]. In cases with multi-segmental involvement and longer fusion spans, however, there are higher rates of complications such as pseudarthrosis and bone graft displacement with subsequent kyphotic deformation [3].…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Several authors have suggested bed rest and prolonged external bracing rather than placing spinal instrumentation 1,12) . Others have advocated a staged instrumented operation with a period of antibiotics therapy after debridement only surgery 4,17,19) .…”
Section: Introductionmentioning
confidence: 99%
“…Due to its non-specific character of symptoms and rare incidence vertebral osteomyelitis is often diagnosed with a delay of several weeks or even months [1][2][3][4][5][6][7][8][9][10][11][12][13]. In up to 50% of patients, neurologic deficits are present at the time of diagnosis [3].…”
Section: Introductionmentioning
confidence: 99%
“…The surgical techniques range from anterior debridement and interbody fusion [1,2,5,[14][15][16][17], posterior debridement with internal fixation [6] to combined single-session or sequential procedures with posterior instrumentation, anterior debridement, and anterior column reconstruction using autologous bone grafts [3, 4, 7-10, 13, 18-23]. Anterior instrumentation in the presence of infection has been reported [21,24,25] but still remains controversial due to the risk of bacterial adherence and biofilm formation on foreign bodies leading to persistent or recurrent infection [4,[26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%